Radiological assessment of pulmonary vascular changes and gastrointestinal changes in patients with COVID-19 referred to a tertiary health care center in Chennai, India: a prospective cross-sectional study - Sathishkumar, Hariharan; Faizal, Afwaan; Majith, Abdul; Raj, Vishnu; Venkataramani, Agathiyanathan (Digital diagnostics, 2024)
BACKGROUND: The coronavirus disease pandemic (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, has led to significant morbidity and mortality worldwide since its emergence in 2019. Although primarily a respiratory illness, COVID-19 can also affect other organ systems, including the vascular and gastrointestinal systems. COVID-19 is linked to both venous and arterial thrombosis, and numerous studies have indicated a heightened risk of pulmonary embolism. Autopsies have revealed pulmonary vasculature thrombosis and bowel ischemia in patients with COVID-19. AIM: To assess radiological pulmonary vascular changes, specifically pulmonary embolism, and gastrointestinal changes in patients with COVID-19 referred to a tertiary healthcare center in Chennai, India. MATERIALS AND METHODS: Computed tomography pulmonary angiography and contrast-enhanced computed tomography of the abdomen were conducted in 100 patients with COVID-19 who met the selection criteria. A radiologist with 5 years of experience evaluated pulmonary vascular and bowel changes. Subsequently, statistical analysis was performed to determine the significance of the relationship between patients with COVID-19 and the occurrence of pulmonary vascular and bowel changes. RESULTS: In this study, 11 patients exhibited pulmonary thromboembolism, and 7 showed significant bowel changes such as bowel wall thickening, mesenteric ischemia, and omental infarction, indicative of potential gastrointestinal involvement of patients with COVID-19. A positive correlation was found between pulmonary embolism prevalence in patients with COVID-19. Pulmonary embolism was diagnosed at a mean of 11 days from disease onset. Of the 24 patients with severe acute respiratory illness, 7 showed pulmonary embolism, detected by computed tomography pulmonary angiography. In addition, of the 10 patients on mechanical ventilation, pulmonary embolism was found in 7. Among the seven patients with bowel changes, four had pulmonary embolism, as detected by computed tomography pulmonary angiography, indicating a significant association between the two concomitant complications. The observed bowel changes were attributed to intravascular thrombosis. CONCLUSIONS: Based on our findings, pulmonary emboli and bowel changes often occur in patients with COVID-19. Multivariate analyses also revealed a connection between invasive mechanical ventilation and pulmonary embolism. The results indicate that patients with severe COVID-19 may also experience concurrent acute pulmonary embolism. Thus, for these patients, the use of contrast-enhanced computed tomography instead of standard non-contrast computed tomography may aid in treatment decision-making.